Rancang Bangun Data Warehouse (Studi Kasus) di PDAM Kabupaten Cilacap - , ISA BAHRONI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Accurate and fast decision making process is highly needed as information technology is advancing. Facilities to prepare, store and use crucial data is needed in strategic decision making process. These data processing facilities are crucial in storing all the necessary information accumulated by the company which later on can be summarized. Data Warehouse is highly needed to improve the company performance. The goal of this research is the create Data Warehouse based on the needs in PDAM in Cilacap Regency. The creation of Data Warehouse Architecture uses Framework Data Warehouse and the Database Cycle which is illustrated using the star schema with the objective to easily understand and use the available information. This development architecture is created based on the present operational condition of the company. Several things which must be noted are that it must be user friendly in its interface and information flexibility. The adopted method is the SDLC method which is divided into several stages: The planning phase needs assessment, solution and architectural design, construction, deployment and maintenance. The planning phase is done through the identification of problems, identifying the system objective and the feasibility study. The next phase is the analyzing of needs which is done by analyzing the current usage of information within the company, determining the user needs and the system. The software architectural design phase is done by designing the database system by creating the activity diagram, DFD, and persistent data. The construction phase is done through the system implementation and development in the form of prototype. The deployment phase is done through deploying the system that has been developed. The maintenance phase is done by maintaining the system by focusing on information and technology update. The final result as the presentation media is in the form of web-based system application development which creates the smooth work-flow and is engineered to be easily accessed with the purpose to get benefits from the sources of information. The system of strategic decision making process can be implemented quickly to give fast services as part of productive decision process.